Memory Activism : Reimagining the Past for the Future in Israel-Palestine - Gutman, Yifat, 1977- (Book collections on Project MUSE., 2017)
Set in Israel in the first decade of the twenty-first century and based on long-term fieldwork, this ethnographic study offers an analysis of the Israeli-Palestinian conflict. It explores practices of "memory activism" by three groups of Jewish-Israeli and Arab-Palestinian citizens -- Zochrot, Autobiography of a City, and Baladna -- showing how they appropriated the global model of truth and reconciliation while utilizing local cultural practices such as tours and testimonies.